UK at the Crossroads: The Impact of No-Deal Brexit on the UK Future Trade with the EU (1950s-2020) - SOUSSANE, Ahmed (My University, 2020)
The aim of this work is to discuss the impact of no-deal Brexit on the United Kingdom (UK) future trade with the European Union (EU). The UK was known as a Euro-sceptic country and the British people had always opposed the European institutions and the European policies. The 2016 referendum finally gave them the chance to the British people to say their opinion about the European integration. The majority express their opinion about the European integration and the majority of the voters made it clear that the UK had to leave the Union. In addition, this work also examines the reasons behind the British desire to leave the EU and the events that happened after the Brexit. The negotiations about the future relationships between the UK and the EU had been started when former British Prime Minister Theresa May triggered the Article 50. There are many options for the future trade relationship between the United Kingdom and the Bloc. If they do not sign any trade agreement before 31 December 2020, the United Kingdom will fall back on the rules of the World Trade Organisation (WTO). The UK exports and imports will be impacted after the Brexit. The UK will be regarded as a third country by the Union, and tariffs will be applied on most its exports and it will also apply tariffs on its imports from the bloc.
Keywords: United Kingdom; European Union; Brexit; Eurosceptic, Integration; Trade; Article 50; World Trade Organisation